2015
DOI: 10.1016/j.sbspro.2015.02.143
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Perceptions While Enrolling in Transnational Study Programs

Abstract: One of the desiderata of the European Higher Education Area is the internationalization of the study programs. The usual arguments for the attractiveness of transnational programs cover aspects like: broader recognition of diplomas, more teaching and learning resources etc. To go deeper than such arguments, this paper will explore the expectations and concerns of students enrolled in 10 universities, in the European Master in Adult Education within the ESRALE project ("European Studies and Research in Adult an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…The openness of the students towards the NTIC can create new opportunities to creatively use virtual learning communities and other instruments especially in transnational study programs (Aristovnik, 2012;Strungă, & Florea, 2014;Sava & Danciu, 2015;Stoian, A.C., 2016), as other studies have shown. We agree with Al Zahrani and Laxman that "M-learning can only bring about an improvement in learner outcomes when it is matched by the application of pedagogical practices that take into account the characteristics and opportunities presented by m-learning and recognize the demands of the differentiated educational and cultural contexts it will be used in" (Al Zahrani & Laxman, 2015, p.86).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The openness of the students towards the NTIC can create new opportunities to creatively use virtual learning communities and other instruments especially in transnational study programs (Aristovnik, 2012;Strungă, & Florea, 2014;Sava & Danciu, 2015;Stoian, A.C., 2016), as other studies have shown. We agree with Al Zahrani and Laxman that "M-learning can only bring about an improvement in learner outcomes when it is matched by the application of pedagogical practices that take into account the characteristics and opportunities presented by m-learning and recognize the demands of the differentiated educational and cultural contexts it will be used in" (Al Zahrani & Laxman, 2015, p.86).…”
Section: Discussionmentioning
confidence: 96%
“…And this observation should not necessarily be limited to m-learning, insofar is relevant even for the larger field of CBIE especially in relationship to adult and distance education programs (Strungă & Martin, 2012;Sava & Danciu, 2015). In delivering educational programs that integrate CBIE, studies have clearly demonstrated that training, support and fidelity of implementation are highly correlated with greater attainment (Archer et al, 2014).…”
Section: Discussionmentioning
confidence: 97%
“…are fare from being solved (Palomares, Pietkiewicz, 2015, European Commision, 2015, UEFISCDI, 2013. The different cultural contexts in different universities are also challenges to be overcome, as they influence the teaching-learning situation, the relation studentteacher/ student-student (Sava, Danciu, 2015, European Union, 2014, Hoare, 2013. Also, the students even are not very optimistic about added value on the labor market, considering that the employers will not necessary appreciate higher an international master, they value such master offer mainly for their personal development, as they are concern with a better understanding of the global issues, as other studies are also underlining (Soria, Troisi, 2014, Lehtomäki, Moate, Posti-Ahokas, 2015, Foster, Yaoyuneyong, 2016, with implications on their level of competence and expertise at the future working place as well.…”
Section: Discussionmentioning
confidence: 99%